Development of Environment-Based Practical Guidelines in Acid-Base Learning - Rizkia, Noviza; Angin, Keumala Fitri Dewi (MANDAILING GLOBAL EDUKASIA, 2024)
Development of environmentally based practicum guides was motivated by the lack of use of practicum guides as support for practicum learning and also the practicum learning at Madrasah Aliyah Swasta (MAS) Al- Kautsar Al-Akbar Medan which were inadequate, such as learning that were no longer usable/expired so they could not be used. during practicum. Research on the development of an environmentally based practicum guide on acid base learning at MAS Al-Kautsar Al-Akbar Medan aims to determine the validity of the practicum guide, teacher responses and student responses to the environmentally based practicum guide developed on acid base material at MAS Al-Kautsar Al -Akbar Medan. This research uses the research and development method (Research and Development/R&D) referring to the ADDIE development model, the stages that researchers must carry out include the analysis stage, the design stage, the development stage, the implementation stage (implementation), as well as the evaluation stage. The results of the research obtained in calculating the average percentage of validator assessments were 82.6% for the teacher response questionnaire, 98% while for students it was 95%. Based on the results of the data obtained, it can be concluded that the environmentally based practicum guide on acid-base material is very valid for use at MAS Al-Kautsar Al-Akbar Medan.